2021
DOI: 10.1016/j.redox.2021.101949
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin reveals therapeutic anticancer potential by triggering distinct molecular cell death mechanisms and innate immunity in mutant p53 non-small cell lung cancer

Abstract: Auranofin (AF) is an FDA-approved antirheumatic drug with anticancer properties that acts as a thioredoxin reductase 1 (TrxR) inhibitor. The exact mechanisms through which AF targets cancer cells remain elusive. To shed light on the mode of action, this study provides an in-depth analysis on the molecular mechanisms and immunogenicity of AF-mediated cytotoxicity in the non-small cell lung cancer (NSCLC) cell line NCI–H1299 (p53 Null) and its two isogenic derivates with mutant p53 R175H or R273H accumulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 86 publications
4
63
0
Order By: Relevance
“…Other findings indicate that both treatments are linked to ferroptosis which is triggered by ROS accumulation, leading to iron-mediated lipid peroxidation and cell death [39,48]. Recently, our research group also demonstrated the induction of ferroptosis and apoptosis in non-small cell lung cancer after AF treatment [42]. However, we are the first to show that the combination of both treatment types sensitizes GBM cells for apoptotic and ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Other findings indicate that both treatments are linked to ferroptosis which is triggered by ROS accumulation, leading to iron-mediated lipid peroxidation and cell death [39,48]. Recently, our research group also demonstrated the induction of ferroptosis and apoptosis in non-small cell lung cancer after AF treatment [42]. However, we are the first to show that the combination of both treatment types sensitizes GBM cells for apoptotic and ferroptotic cell death.…”
Section: Discussionmentioning
confidence: 63%
“…Contrary to DFO, the level of protection against cell death by Fer-1 was incomplete, as Fer-1 failed to protect cells from lipid peroxidation. Previously, we already showed that DFO and Fer-1 were able to partially prevent cell death in non-small cell lung cancer after AF treatment alone [42]. Excessive ROS, induced after combination treatment of AF and pPBS, could explain this incomplete protection of Fer-1 [43].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that proteins in complex have higher thermal stability than their dissociated counterpart [ 64 ]. Recently, Boullosa et al [ 65 ] have shown that AF increases DNA damage in cancer cells. Lower activity of MCMBP leads to genome instability and increased DNA damage [ 62 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PISA analyses highlighted EEFSEC, GSK3A and GSK3B and MCMBP as target hits of AF, which would explain at least in part the downregulation of selenoproteins, metabolic effects, anti-inflammatory effects and DNA damages that are typically and specifically observed upon AF treatment. These processes have been previously described in AF treatment, but their molecular foundations have remained elusive [ 47 , 65 ]. TRi-2 target hits were here found to also include four members of the aldo-keto reductase family, thus potentially increasing the therapeutic potential of this compound in therapies targeting these enzymes and in other diseases than cancer [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ferroptosis, as a unique iron-dependent form of regulated cell death characterized by overwhelming lipid peroxidation due to accumulation of reactive oxygen species (ROS) (Doll et al, 2017;Yang et al, 2014; J. Zheng & Conrad, 2020), which differs from others such as apoptosis, necrosis and autophagy in respects of morphology, genetics and biochemistry (Dixon et al, 2012), is involved in the pathological process of lung cancer cell proliferation, migration and prognosis (Han et al, 2021; C. Y. . Meanwhile, the adjustable sensitivity of lung cancer cells to ferroptosis by pharmacological strategies can affect the outcomes of lung carcinoma (Alvarez et al, 2017;Freire Boullosa et al, 2021). Overexpression of ΔNp63α protects LUSC from oxidative damage-induced ferroptosis to implement cancer cell with high viability (G. X.…”
Section: Introductionmentioning
confidence: 99%